Assessing Self-Confidence in Career Readiness Among Prospective English Education Study Program Graduates of University - Kondo, Nadia; Siumarlata, Victor; Tandikombong, Matius (Institut Agama Islam Negeri Palopo, 2024)
This study addresses the issue of confidence among prospective graduates of the English Education Study Program at UKI Toraja as they prepare to enter the workforce. The research aims to find out the level of self-confidence in the career readiness of prospective English education study program graduates of UKI Toraja. The researcher employed a quantitative descriptive method in analyzing the data of this research. The subjects of this research were the seventh-semester students of the English education study program, UKI Toraja, who programmed the thesis. The data of this research was collected by questionnaire to gather data from 20 participants. The data obtained were analyzed using Likert scale techniques. The findings indicate that the overall level of self-confidence among these prospective graduates falls into the category of fair self-confidence, with an average score of 75.5% for the educator category, 68.8% for the entrepreneur category, and 68.1% for the tourism industry category. The implications of this study's results indicate that although students' self-confidence is in the fair category, there is still a need for improvement. Therefore, it is important for study programs to develop strategies that can increase student confidence so that they are better prepared for their readiness for a career. Keywords: Assessing; Self-Confidence; Career; Readiness